PERANCANGAN ARSITEKTUR ENTERPRISE PADA BADAN PENDAPATAN DAERAH PROVINSI JAWA BARAT DI BIDANG PENGENDALIAN DAN EVALUASI PENDAPATAN MENGGUNAKAN TOGAF - Syaffa, Naura Imanda; Fajrillah, Asti Amalia Nur; Hanafi, Ridha (Universitas Negeri Padang, 2023)
The use of information systems in electronic-based government systems (SPBE) has become the main focus in an attempt to enhance the quality of public services in Indonesia. Bapenda West Java Province is one of the organizations responsible for managing regional revenue and providing services to the public. This research aims to design an enterprise architecture in the Revenue Control and Evaluation Division of the West Java Provincial Revenue Agency using TOGAF. This research was conducted as an attempt to enhance the quality of public services through the implementation of information technology in the Electronic-Based Government System (SPBE). Currently, the evaluation of SPBE in West Java Province shows a